Dipeptidyl peptidase IV inhibitors derived from a mangrove flora Rhizophora mucronata: An in silico approach - Gurudeeban, Selvaraj; Satyavani, Kaliyamurthi; Ramanathan, Thirugnanasambandam; Ravikumar, Palanisamy (Bangladesh Journal of Pharmacology, 2012)
Dipeptidyl peptidase IV (DPP IV) is responsible for conversion of glucose tolerance (GLP-1), into inactive form. The inhibition of DPP IV would be beneficial in the treatment of diabetes mellitus. Therefore, the aim of the present study was to isolate and evaluate cystine, phenyl acetic acid, acrylamide, caprylone and oleic acid from Rhizophora mucronata inhibitory action on DPP IV inhibitors using in silico approach. In silico analysis of cystine, phenyl acetic acid, acrylamide, caprylone and oleic acid on human apo DPP IV protein was done by using Autodoc 4.0. Among the five compounds cysteine acts as an inhibitor with binding energy -5.89 kcal/mol, seven hydrogen bond interactions at residues VAL459, VAL 459, GLU408, GLU206, ARG358, GLU205 and SER209 to suppresses the action of DPP IV protein.